New Recursive Representations for the Favard Constants with Application to Multiple Singular Integrals and Summation of Series - Snezhana Georgieva Gocheva-Ilieva; Ivan Hristov Feschiev (Abstract and Applied Analysis)
There are obtained integral form and recurrence representations for some Fourier series and connected with them Favard constants. The method is based on preliminary integration of Fourier series which permits to establish general recursion formulas for Favard constants. This gives the opportunity for effective summation of infinite series and calculation of some classes of multiple singular integrals by the Favard constants.